He Shoots, He Stores: New Photographic Practice in the Digital Age - Bushey, Jessica (Archivaria, 2008)
In the last decade, professional photographers have responded to changing business needs and creative opportunities by transforming their analogue-based processes and products into a predominantly digital-imaging practice. The fundamental differences between the creation and preservation of analogue photographs, and the creation and preservation of digital images have moved beyond issues of media stability and now focus on the changing role of the photographer as both creator and preserver. Central to this discourse is the relationship among the concepts of originality, reliability, and authenticity in regards to photographic representation in the digital era. This article contributes to that discussion by presenting the results of an InterPARES 2 survey on the record-keeping activities of photographers using digital technology; presenting new developments instigated by the imaging community to address issues of digital-image creation, use, and preservation; and exploring how the digital paradigm shapes the responsibilities of the archivist. RÉSUMÉ Au cours de la dernière décennie, les photographes professionnels ont répondu aux nouveaux besoins du monde des af faires et aux possibilités créatives en s’éloignant des procédés et produits analogues pour adopter une pratique basée principalement sur les images numériques. Les dif férences fondamentales entre la création et la préservation de photographies analogues et la création et la préservation d’images numériques vont maintenant plus loin que les questions de stabilité du support et se concentrent davantage sur le nouveau rôle du photographe tant comme créateur que comme conservateur. Les liens entre les concepts d’originalité, de fiabilité et d’authenticité par rapport aux représentations photographiques dans l’ère du numérique sont au centre de ce discours. Ce texte y contribue en présentant les résultats d’un sondage InterPARES 2 sur les activités de gestion de documents des photographes qui se servent de la technologie numérique; il présente des nouveaux développements initiés par la communauté de l’imagerie pour répondre aux questions liées à la création, à l’utilisation et à la préservation des images numériques; il explore enfin comment le paradigme numérique définit les responsabilités de l’archiviste.